Critical Spiritualism in a Collection of Short Stories “Markesot Bertutur Lagi” by Emha Ainun Nadjib: Dialogical Analysis of Mikhail Bakhtin - Akbar Rezki Ramadhan; Anshari Anshari; Suarni Syam Saguni (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract.  This study aims to identify the carnivalization and critical spiritualism present in the short story collection Markesot Bertutur Lagi using Bakhtin's dialogical perspective. This study uses a qualitative data analysis design with descriptive data presentation. The data was obtained through the literature study method. The results of this study are: 1) carnivalization and composition; 2) the character and position of the author. From this description, the results of the study describe that from a perspective on the relationship with components of the short story collection of Markesot Bertutur Lagi, it does not guarantee itself that it is fully polyphonic and dialogical, but seeing as a whole from certain parts using Bakhtin's dialogic, that in addition to novels, short stories collections can also has criteria for polyphonic or dialogical literary works that have carnivalistic elements. Seeing also from a dialogical perspective and also the results of the reading, it is found that critical spiritualism that occurs is the view of people's doubts about Marketing and Marketing's new perspective which actually holds fast to their religious understanding and knowledge based on the Qur'an and the Hadith of Muhammad SAW. . Based on the results of this study, it is recommended for Indonesian Language and Literature Students to apply and develop the study of Mikhail Bakhtin's Dialogical theory.Keywords: Dialogis, Spiritualisme Kritis, Dogmatis, Skeptis